INEQUALITY AND CRIMINALITY REVISITED: FURTHER EVIDENCE FROM BRAZIL - Adolfo Sachsida
The objective of this study is to shed light on the determinants of criminality in Brazil. In order to undertake it we performed an econometric model based in panel data analysis for Brazilian states: Among the major conclusions we have an important result that income inequality plays an important role in criminality. Results also showed that unemployment and urbanization are positively related to crime factors. Based in panel data GMM methodology we found the existence of "inertial effect" on criminality. Panel data GMM estimator was also used to control the existence of endogeneity related to the variable public security. In this case, the results showed that public security spending is effective to diminishes criminality. Contrary to the common wisdom, we cannot found evidence that poverty increases violent crime. Finally considering the results from the Granger causality tests, it was possible to show that inequality causes crime in fact and not the contrary, what supports that the income inequality in an inequivocous determinant of criminality.